PENGOPTIMALAN METODE RESITASI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AL-QUR`AN HADIST DI MADRASAH MIFTAHUL ULUM BATURETNO SINGOSARI MALANG - Choirudin, Arif Choirudin; Mutholingah, Siti Mutholingah (STAI Ma'had Aly Al-Hikam Malang, 2022)
Teaching and learning activities are very important in the world of education, this requires the right method. Namely, the recitation method is a suitable method for optimizing learning outcomes, one of which is in the subjects of Al-Qur`an Hadith which is located at Madrasah Miftahul Ulum, Baturetno Singosari village, Malang. One of the objectives of this research is to describe the use of the recitation method in optimizing student learning outcomes in the subjects of the Qur'an Hadist. The approach used in this research uses a qualitative approach of case study type. Data collection researchers used the method of observation, interviews, documentation. Meanwhile, the data analysis used is the Miles and Hubermen model. The results of the research: (1) The Learning Planning Stage is in the form of preparing lesson plans and planning smart classes. (2) Learning Implementation Stage: presentation of material, questions and answers, assignment, guidance on task results. (3) The Learning Evaluation Stage includes a written test and an oral (memorization) test. The obstacles faced were 2: From students; lack of students' ability to read the Qur'an, lack of motivation, from the teacher; mastery of learning methods. The impact of using the recitation method is 2: a) the impact of understanding; students are more independent, students' insight is wider. b) The impact of increasing learning outcomes: students are more independent in assignments, students are serious about the tasks given.